(untitled) - Harvey, D R (Munich, 2005)
Digital preservation is an issue faced by practitioners in the library and recordkeeping professions, yet most professionalshave little time to keep up with the latest techniquesand standards. This invaluable work provides asingle-volume introduction to the principles, strategies and practices currently applied by librarians and recordkeepers to the preservation of digital information and will assist them to make informed decisions about the role of digital information in their care
Keywords: Digital preservation,Electronic information resources,Digital libraries,Bảo tồn tài liệu số,Nguồn thông tin điện tử,Thư viện số; Collection and preservation,Bộ sưu tập và bảo quản